Enhancement of resilience of coastal community in Bangladesh through crop diversification in adaptation to climate change impacts - Rahman, Md. Mizanur (BRAC University, 2013)
This dissertation is submitted in partial fulfillment of the requirements for the degree of Master in Disaster Management, 2012.